- LAA Occluder View for post-implantation Evaluation (LOVE) - standardized imaging proposal evaluating implanted left atrial appendage occlusion devices by cardiac computed tomography. Issue 1 (December 2016) - Behnes, Michael; Akin, Ibrahim; Sartorius, Benjamin; Fastner, Christian; El-Battrawy, Ibrahim; Borggrefe, Martin; Haubenreisser, Holger; Meyer, Mathias; Schoenberg, Stefan; Henzler, Thomas
Abstract Background A standardized imaging proposal evaluating implanted left atrial appendage (LAA) occlusion devices by cardiac computed tomography angiography (cCTA) has never been investigated. Methods cCTA datasets were acquired on a 3rd generation dual-source CT system and reconstructed with a slice thickness of 0.5 mm. An interdisciplinary evaluation was performed by two interventional cardiologists and one radiologist on a 3D multi-planar workstation. A standardized multi-planar reconstruction algorithm was developed in order to assess relevant clinical aspects of implanted LAA occlusion devices being outlined within a pictorial essay. Results The following clinical aspects of implanted LAA occlusion devices were evaluated within the most appropriate cCTA multi-planar reconstruction: (1) topography to neighboring structures, (2) peri-device leaks, (3) coverage of LAA lobes, (4) indirect signs of neo-endothelialization. These are illustrated within concise CT imaging examples emphasizing the potential value of the proposed cCTA imaging algorithm: Starting from anatomical cCTA planes and stepwise angulation planes perpendicular to the base of the LAA devices generates an optimalL AAO ccluderV iew for post-implantationE valuation (LOVE). Aligned true axial, sagittal and coronal LOVE planes offer a standardized and detailed evaluation of LAA occlusion devices after percutaneous implantation. Conclusions This pictorial essay presents a standardized imaging proposal by cCTA using multi-planar reconstructions that enables systematical follow-up and comparison of patients after LAA occlusion device implantation.